Counteraction to information influence in social networking services by means of fuzzy logic system - Kateryna Molodetska; Vladyslav Solonnikov; Oleksandr Voitko; Ihor Humeniuk; Oleksandr Matsko; Oleksii Samchyshyn (Institute of Advanced Engineering and Science, 2021)
The article describes a decision support system based on fuzzy inference aimed to automate the procedure of choosing a model of formalizing the interaction between actors in virtual communities of social networking services and synergistic management of such processes. The developed system aims to increase the effectiveness of counteracting threats to information security of the state in social networking services. The mathematical apparatus of the fuzzy set theory and the Mamdani algorithm are the basis for the functioning of the decision support system. The usage of the developed fuzzy inference system will remove the ambiguity of information security expertise in the course of choosing approaches to formalization and the model of synergistic management of actors’ interaction in the conditions of incomplete information and ambiguous assessment of the state information security threat in social networking services.